INDIVIDUAL COUNSELING SERVICES TO ADDRESS THE TRAUMA OF ADOLESCENT VICTIMS OF SEXUAL ABUSE THROUGH ISLAMIC THERAPY - YULIA SARI; MUHAMMAD PUTRA DINATA SARAGI; FIRLY SYAHIRA SIHOMBING; INDAH SARI; PUTRI RAHMADANI PANJAITAN (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
Sexual harassment is a bad act that can reduce human dignity, both women and men. The rise of the problem of sexual harassment can occur among teenagers. Victims of sexual harassment will usually experience mental wounds that can affect their mental and psychological states that take time to heal, such as experiencing trauma. The sense of trauma that exists in adolescents will make them into shock, and it needs to be handled through Islamic therapy. This study aims to overcome the trauma of adolescents who are victims of sexual harassment. This study uses a qualitative approach with data collection techniques through observation and interviews. The result of this study has shown that the application of individual counseling services by applying Islamic therapy can overcome trauma in one of the teenage boys who became victims of sexual harassment. The application of Islamic therapy has been carried out using faith therapy so that the teenager will get peace and inner peace and become a person who always increases faith or draws closer to Allah Swt. by enjoining ma'ruf nahi munkar.